5w+7-2(-7w-4)=3(w-1)

Simple and best practice solution for 5w+7-2(-7w-4)=3(w-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5w+7-2(-7w-4)=3(w-1) equation:


Simplifying
5w + 7 + -2(-7w + -4) = 3(w + -1)

Reorder the terms:
5w + 7 + -2(-4 + -7w) = 3(w + -1)
5w + 7 + (-4 * -2 + -7w * -2) = 3(w + -1)
5w + 7 + (8 + 14w) = 3(w + -1)

Reorder the terms:
7 + 8 + 5w + 14w = 3(w + -1)

Combine like terms: 7 + 8 = 15
15 + 5w + 14w = 3(w + -1)

Combine like terms: 5w + 14w = 19w
15 + 19w = 3(w + -1)

Reorder the terms:
15 + 19w = 3(-1 + w)
15 + 19w = (-1 * 3 + w * 3)
15 + 19w = (-3 + 3w)

Solving
15 + 19w = -3 + 3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-3w' to each side of the equation.
15 + 19w + -3w = -3 + 3w + -3w

Combine like terms: 19w + -3w = 16w
15 + 16w = -3 + 3w + -3w

Combine like terms: 3w + -3w = 0
15 + 16w = -3 + 0
15 + 16w = -3

Add '-15' to each side of the equation.
15 + -15 + 16w = -3 + -15

Combine like terms: 15 + -15 = 0
0 + 16w = -3 + -15
16w = -3 + -15

Combine like terms: -3 + -15 = -18
16w = -18

Divide each side by '16'.
w = -1.125

Simplifying
w = -1.125

See similar equations:

| 5(3x-4)=0 | | 4a^2+10a-22=0 | | 14c-6c= | | -11+6+7n-9n=n+1 | | 4x-2(5x-8)=-56 | | (6x)=6(xy) | | 2m^2-7m-7m-13=-10 | | 5w-5+2(3w+7)=-5(w+1) | | 15u-8u=49 | | 6=4x/(12-x) | | X-2(-.3)=2 | | 13=5x+11 | | 3n+2=3 | | 3(2+2y)+4y=3 | | 7+4q=11+34 | | 6+6x=6(x-5) | | 7(x+4)=-2(5x-5)+2x | | (2x+1)-(-4x-9)= | | x+3x+6x=3450 | | 12(10)+3(14)=162 | | 9-x=x+12 | | 7-2n=4 | | 8(10)+3(14)=122 | | 4z-5=8x+3 | | -3(-2w+3)-9w=3(w-7)-3 | | 2y(y)=400 | | 2.1x-12.2= | | 481.194=13.4*6.3*w | | 3x-4+2x+10=21 | | -12/5=-6u | | -3(2x-4)=5x | | 3x+7-9+x=2x+3-x+4 |

Equations solver categories